EIGEDOM RIGHTS AS A PERFECT GUARANTEE OF INDIVIDUAL RIGHTS TO OWNERSHIP - Mauliana, Awanda Luthfia Dwi; Handoyo, Dede Sidiq; Zahra, Syifa Amalia; Erowati, Eti Mul; Pudyastiwi, Elisabeth (Cattleya Darmaya Fortuna, 2025)
Eigendom, derived from Dutch, means